Developing creativity in mathematics instruction - Vasojević, Irena; Krnjaić, Zora; Vasojević, Nena (Nastava i vaspitanje : časopis Pedagoškog društva SR Srbije i Pedagoškog društva SR Črne Gore, 2021)
This paper aims to highlight the importance and the possibilities of developing creativity and creative thinking in mathematics instruction. One of the key tasks of the educational process in schools is the stimulation and development of students' creative abilities. Students' creative abilities and divergent forms of working with them are not restricted to specific areas and fields of human activity; rather, it is a matter of the specific and distinctive qualities of the development of creativity and creative expression in certain areas, or school subjects. The paper examines the need and the possibilities of developing creative thinking in children of primary school age and in mathematics instruction in the lower and upper grades of primary school, since creativity is not linked exclusively to art or certain fields or school subjects, nor is it the privilege only of gifted and talented children and students.